Ground Water in the City of Varanasi, India: present status and prospects - Mohan, Kshitij; Srivastava, Ajai; Rai, Praveen Kumar (Quaestiones Geographicae, 2011)
The city of Varanasi is short of water. The city obtains a total of 270 million litres water from the river Ganga and tubewells. Yet every fifth citizen lacks drinking water. The ground water is polluted due to nitrate and faecal coliform. A further problem is the plan to settle the growing population in a new township nearby under the integrated development plan of Greater Varanasi, a part of the Jawajarlal Nehru Urban Renewal Mission. To fulfill the growing demand of fresh water, new water bearing horizon of the most affected part of the city i.e. southern part is to be identified. This paper reports a study of the variation in the grain size attributes of an aquifer material taken from different depths from the affected region in order to establish the generalized hydrological properties and recommend the depth of the well accordingly. From the grain size analysis and hydrological study it may be concluded that water bearing zones are mainly found in three horizons at the depths 44-56 m; 56-87 m; and 87-165 m. The third water bearing horizon (total thickness being 78 m) can act as a good potential ground water horizon for a new township. Due to its greater depth, the water would be relatively fresh being characterized by very low concentration of dissolved solids. Therefore, this horizon is strongly recommended for utilizing the water resource for the township.